Redescription of Dasythrix inornata (Loew, 1851) (Diptera: Asilidae: Laphriinae) with a new synonym and new distribution records - Camargo, Alexssandro; Vieira, Rodrigo; Rafael, José Albertino (Zootaxa, 2021)
The holotype of Dasythrix inornata (Loew, 1851) is redescribed and illustrated. Male terminalia are described and illustrated for the first time. Dasythrix leucophaea Lynch Arribálzaga, 1880 syn. nov., is synonymized with D. inornata. Consequently, Dasythrix is a monotypic genus. New distribution records are provided. Laphria heteronevra Macquart, 1838, currently placed in Laxenecera Macquart, 1838, has its previous combination with Nusa Walker, 1851 revalidated, becoming Nusa heteronevra (Macquart, 1838) comb. rev. The status of Dasythrix Loew, 1851 is also discussed. Copyright © 2021 Magnolia Press.